IMPLEMENTASI KURIKULUM MATA PELAJARAN EKONOMI DI SMA ISLAM TERPADU AL-FITYAN KUBU RAYA - Muhjanah, Fea; Mashudi, Mashudi; Witarsa, Witarsa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is entitled "Implementation of the Integrated Islamic Curriculum in Economic Subjects at SMAIT Al Fityan Kubu Raya". This research is a qualitative research that describes the conditions of the subject and research object.The Integrated Islamic School Network Curriculum (JSIT) is a curriculum that integrates the curriculum with the National curriculum based on Islamic education. The purpose of this research is to examine the implementation of the Integrated Islamic School (SIT) curriculum at SMAIT Al-Fityan Kubu Raya, which is realized in Graduate Competency Standards, Content Standards, and Process Standards. The research design of this research is qualitative research. The main data sources were obtained through interviews, observation and documentation. And data analysis techniques obtained from data reduction, data presentation and data verification by conducting data triagulation. The results of this study show that the implementation of the SIT curriculum at SMAIT Al-Fityan shows indications of the internalization of Islamic values in all subjects, especially in Economics. With reference to the standards of the Integrated Islamic Curriculum.